Comprehensive management of erectile dysfunction in diabetes mellitus: pathogenesis, treatment modalities, and future perspectives - Dróżdż, Olgierd; Dołęga, Marcin; Gacka, Piotr; Musialska, Dominika; Grzelka, Michalina (Quality in Sport, 2024)
Diabetes mellitus (DM) significantly increases the risk of erectile dysfunction (ED), affecting up to 52% of diabetic males. This review examines the epidemiology, pathophysiology, and treatment modalities of ED in diabetic patients. Key factors influencing ED in this population include poor glycemic control, obesity, hypertension, and the duration of diabetes. Both the latest reports on treatment and well-known articles containing fundamental knowledge about this condition were analyzed, mainly using online databases like PubMed. Effective management of ED in diabetic patients requires optimal glycemic control and lifestyle modifications such as diet, exercise, and weight management. Pharmacological treatments involve phosphodiesterase type 5 (PDE5) inhibitors like sildenafil, tadalafil, and vardenafil, which enhance erectile function by increasing cGMP levels. Alternatives for those unresponsive to oral medications include intracavernous injections, intraurethral alprostadil, vacuum constriction devices, low-intensity extracorporeal shock wave therapy (Li-ESWT), and penile prosthesis implantation. Emerging therapies like mesenchymal stem cell therapy and novel drug combinations offer promising avenues, focusing on cellular regeneration and improved vascular function. Despite the availability of these treatments, ED remains underreported due to patient embarrassment and healthcare provider hesitation, underscoring the need for increased awareness and proactive management. As projections indicate a rising global prevalence of ED, integrating ED management into comprehensive diabetes care is essential to enhance patient quality of life and address this significant public health issue.